Enhancing Agricultural-Based Entrepreneurial Activity in Cagayan Valley using Technology Business Incubation (TBI) Model - Eva U. , Cammayo; N, Nayga Jonathan; Joy M, Balbin Aubrey; Diosdado C., Canete (International Journal of Psychosocial Rehabilitation, 2020)
Technology Business Incubator (TBI) is a facility where start-ups are hosted and business development services are provided. For would-be technology entrepreneurs and start-ups, the Department of Science and Technology- Philippine Council for Agriculture, Aquatic and Natural Resources Research and Development (DOST-PCAARRD) -funded TBIs to offer technical services, facilities and office space to get their business established. The Cagayan Valley Small Ruminant Research Center (CVSRRC) at Isabela State University (ISU) is one of the first Agri-Aqua TBI in the country. The incubator operates using a model that complements expert, technology and facility. The incubator offered assistance in the form of technical/technological and enterprise counselling; financial and market linkages. During the incubation process, several interventions that are tailor-fitted to the needs of the incubatees were provided. After one-year of TBI operation, 15 incubatees were successfully graduated from the program. Moreover, the R&D facilities at ISU-CVSRRC were transformed into business development hubs that helps to improve business operation at the rural setting. At present, these incubatees have already established their own enterprises thru commercialization of ISU-CVSRRC mature goat technologies and other products and through commercialization of their own products. Because of this, 25 different products were already commercialized, 15 enterprises were established and 98 local employment offered. These outputs thereby facilitate market growth and increase in income from rural-based business. Indeed, the presence of an agricultural TBI facility can be considered as an effective catalyst of industrial, economic and social development and as an important tool to facilitate growth in in the countryside. Thus, in order to assist more entrepreneurs and sustain the initial growth obtained, it is recommended that the incubator should be institutionalized.